Learning about social movements through news media: deconstructing New York Times and Fox News representations of Standing Rock. Issue 4 (4th July 2018) - Walker, Judith; Walter, Pierre
ABSTRACT: This article critically examines how news media, as a form of public pedagogy, functioned to 'educate' the public about the Standing Rock pipeline protests in North Dakota, USA. Drawing on literature in public pedagogy, social movement learning and communication studies, we employed ethnographic content analysis to identify emergent patterns, emphases and themes in all online media coverage by the New York Times and Fox News of the Standing Rock protests from April 2016 to March 2017. We analysed representations of Standing Rock in 164 NYT articles, and 96 Fox News articles, respectively. This ethnographic methodology allowed us to understand how the Standing Rock movement, its actors and meaning were constructed through the use of imagery, metaphors and emphasis on particular voices, narratives and perspectives. Our findings showed how both Fox and NYT were able to effectively frame the protest as a fundamentally human story focusing on Indigenous people, celebrities and US war veterans, and address broad-based public concerns about global climate change, water pollution and land rights. These results point to the importance of mainstream media as public pedagogue shaping social movement learning, and to the need for further research on this topic in adult education.